A practical approach for small bowel bleeding - Sung Eun Kim; Hyun Jin Kim; Myeongseok Koh; Min Cheol Kim; Joon Sung Kim; Ji Hyung Nam; Young Kwan Cho; A Reum Choe (Korean Society of Gastrointestinal Endoscopy, 2023)
Gastrointestinal (GI) bleeding is one of the most common conditions among patients visiting emergency departments in Korea. GI bleeding is divided into upper and lower GI bleeding, according to the bleeding site. GI bleeding is also divided into overt and occult GI bleeding based on bleeding characteristics. In addition, obscure GI bleeding refers to recurrent or persistent GI bleeding from a source that cannot be identified after esophagogastroduodenoscopy or colonoscopy. The small intestine is the largest part of the alimentary tract. It extends from the pylorus to the cecum. The small intestine is difficult to access owing to its long length. Moreover, it is not fixed to the abdominal cavity. When hemorrhage occurs in the small intestine, the source cannot be found in many cases because of the characteristics of the small intestine. In practice, small-intestinal bleeding accounts for most of the obscure GI bleeding. Therefore, in this review, we introduce and describe systemic approaches and examination methods, including video capsule endoscopy and balloon enteroscopy, that can be performed in patients with suspected small bowel bleeding in clinical practice.